A review of the acoustic properties of noise barriers made from waste and plant-based materials - Strazdas, Edgaras; Januševičius, Tomas (International Conference “Environmental Engineering”, 2023)
Noise barriers have been widely used around the world for many years. Solutions are being sought on how waste or plant-based materials can be integrated into the production of barriers, which would not deteriorate the acoustic properties of the barriers, and at the same time comply with the principles of circular economy and sustainability. The aim of the work is to review the currently conducted scientific research related to the development of new generation noise barriers and the use of waste or plant-based materials for their production, as well as to analyse the potential of these materials in acoustics. Materials and barriers made of construction and demolition waste, porous concrete made of waste, combustion bottom ash, tire waste, coconut fiber and straw, palm tree pruning waste, hemp fiber, bamboo was reviewed. The sound absorption and sound insulation properties of barrier constructions and materials are described. After conducting a review of the literature, the materials used for the production of noise barriers were determined, which correspond to the principles of the circular economy, as well as the general trends of structural solutions.